Pengaruh Kecukupan Modal, Fungsi Intermediasi, Pembiayaan Bermasalah, dan Biaya Operasional Terhadap Profitabilitas Indusstri Bank Syariah Periode Januari 2010-Desember 2012 - Maharanie, Mega Ayu; Herianingrum, Sri (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The objectives of this research to analyze the influence of capital adequacy as measured by Capital Adequacy Ratio (CAR), intermediary functions as measured by Non Performing Financing (NPF), financial problems as measured by Financing to Deposit Ratio (FDR), and operational cost as measured by BOPO to profitability as measured by Return On Asset (ROA) of Islamic Banking Industry in the period of 2010-2012. The population used for the study is Islamic banks whose financial statements have been published to Bank Indonesia from 2010-2012. The sampling techniques is cencus sampling, so the sample in this study is every unit in a population. The data of this study used secondary data from the website of Bank Indonesia. The method of data analysis which was used is multiple linier regression analysis.From the result of analyse indicate that CAR, NPF, and BOPO variables has significantly affcet in partial toward ROA at level of significant less than 0,05, but only FDR variable has no significantly affect to the ROA. While, CAR, FDR, NPF, and BOPO variables in simultan has no affect to the ROA with a significance level of 0,000.